Os Aranã e sua indianidade: disputas internas por legitimidade e o reconhecimento oficial como grupo indígena - Lucas Carneiro de Carvalho (2008)
This work encompasses the construction process of the Aranã indigenous groups ethnic identity. The dissertation investigates how this group, when dealing with external agents, constructed its own conception of Aranã indigenousness. However, the group used information and data which were previously unknown to it. One of the central points of this work is to state that the use of external data and information, previously unknown to the group, does not invalidate their ethnic-ity nor their process of regaining their traditions and their history. In the Aranã case, the commu-nity had always affirmed that it was descended of indigenous people of the region, that its ances-tors were capture in the woods. Nonetheless, they did not know their groups ethnic name. It was looking into western historiography that the group managed to (re)discover its indigenous name. Two distinct family groups comprised the Aranã: the Caboclo family and the Índio family. This work investigates how the cooperation between the different families was set and what the common characteristics were which led to the construction of a common identity. However, the relations among the two family groups ended up becoming tense enough to provoke an internal division. The dissertation uses both interviews and documents produced by the Aranã people themselves to investigate how the two families were united, the falling out and, afterwards, the division of the group. When analysing the interviews and the documents, one realises that there are numerous issues behind that which is made explicit. This work makes use of theories and methodologies concerning ethnicity and identity to better approach the Aranã case. As a result, it leads some suggestions as to how to approach similar cases of ethnic and identity.